Diagnosis of Central Retinal Artery Occlusion in the Emergency Department Using POCUS: A Case Series - Nicholas Cozzi; Kendall Stevens; Yeoshina Pillay; David Moore; Matthew Flannigan; Mariah Barnes; Matthew Singh; Melisa Gagrica; Christian Kolacki; Jennifer Bach; Dale McNinch; Drue Orwig; et al. (CINQUILL Medical Publishers Inc., 2021)
Introduction: Central Retinal Artery Occlusion is a cause of vision loss that warrants emergent evaluation. Ocular Point of Care Ultrasound (POCUS) is a non-invasive, inexpensive, and rapid modality to establish diagnosis with reduced time to consultation and treatment. Methods: This was a retrospective case series of patients evaluated at seven hospitals with diagnosis of CRAO over a two-year period. All patients underwent ocular POCUS performed by an emergency medicine clinician.  Results: Nine patients were evaluated with mean vision loss of 21 hours. Overall, 88% of patients were diagnosed with CRAO, 75% possessing US confirmed retrobulbar spot sign (RBBS), and 38% confirmed diagnosis with fundoscopy. Conclusion: Ocular POCUS is an examination all emergency medicine clinicians should be able to perform. A rapid diagnosis of CRAO provides opportunity for vision improvement with initiation of treatment. The lack of guidelines for treatment of CRAO represents an opportunity for a multi-speciality collaboration to develop a diagnostic and treatment algorithm.